Construção automática de redes sociais móveis no ambiente Moodle - Castro, Tássia Portela Serrão de (Universidade do Vale do Rio dos Sinos, 2012)
The traditional teaching methods of the Learning Management Systems (or LMS) are rigid in nature and impose limitations on the teaching process. By having a closed pattern, these tools end up hurting the student, for preventing it from interacting with anyone who shares the same interests as him. For example, the student posts a question about a particular topic in the forum and sometimes wait days, weeks, without getting any return. As a result, the concepts of community, relationship and interaction between users are required to overcome these limitations. Currently Moodle does not provide tools that support the creation of a social network that can be articulated by the participants. The purpose of this study is to develop a social software that enables the creation and articulation of online social networking in Moodle automatically. From this, it is expected that each student can have your own space, with virtual communities of practice specific to their needs, and he can also at any time add new people to these communities, they are everywhere, that is, in any Moodle course, group or forum, extending beyond social networking, the educational possibilities that only collaborative learning provides
Keywords: Aprendizagem colaborativa; Redes sociais online; Sistemas de gerenciamento de aprendizagem; Collaborative learning; Online social networking; Learning management systems; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação